2008
DOI: 10.1590/s1516-31802008000600006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of micronuclei in exfoliated uterine cervical cells from patients with risk factors for cervical cancer

Abstract: CONTEXT AND OBJECTIVE: Pap smears are the most common and inexpensive screening method for cervical cancer. We analyzed micronucleus prevalence in exfoliated cervical mucosa cells, to investigate associations between increased numbers of micronuclei and risk factors for cervical cancer. DESIGN AND SETTING: Analytical cross-sectional study, at Instituto de Pesquisa em Oncologia (IPON). METHODS: Exfoliated cervical cells were obtained from 101 patients between September 2004 and November 2005. Patients' ages, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 43 publications
1
19
1
2
Order By: Relevance
“…The results obtained showed that, patients with one or more risk factors have a higher prevalence rate of micronuclei in exfoliated cells than those without any risk factors. 21 This study results demonstrated a strong association between HPV type infection andMN frequency. MN may comprise an additional criterion for establishing HPV typeinfection and cervical cancer risk.…”
Section: Using Micronucleus In Gynecological Cancer Predictionsupporting
confidence: 56%
See 1 more Smart Citation
“…The results obtained showed that, patients with one or more risk factors have a higher prevalence rate of micronuclei in exfoliated cells than those without any risk factors. 21 This study results demonstrated a strong association between HPV type infection andMN frequency. MN may comprise an additional criterion for establishing HPV typeinfection and cervical cancer risk.…”
Section: Using Micronucleus In Gynecological Cancer Predictionsupporting
confidence: 56%
“…21 The aim was to examine how increased numbers of micronuclei relate to cervical cancer. Cervical mucosa cells were obtained from over 101 patients, with Ayre spatulas.…”
Section: Using Micronucleus In Gynecological Cancer Predictionmentioning
confidence: 99%
“…The micronucleus frequency was significantly higher in women with cervical cancer than in women showing precursor lesions, and this finding did not differ between the various stages of cancer progression. However, Campos et al (2008) described a positive association between micronucleus occurrence and lesion grade. Similar results were reported earlier by Chakrabart and Dutta (1988).…”
Section: Discussionmentioning
confidence: 99%
“…The number of exfoliated cells scored in MN analysis varies from group to group (from 500 to 3,000) [2,7,9,10]. The majority of studies score between 1,000 and 3,000 cells [2], and there are many published studies that scored 1,000 cells [11,12,13,14,15,16]. Pandey et al [13] analyzed 1,000 cells by staining with the DNA-specific dye acridine orange under a fluorescent microscope in borderline cases of cervical dysplasia, and also counted over 1,000 cells.…”
Section: Tablementioning
confidence: 99%